2019
DOI: 10.1186/s12870-019-1936-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide exploration and characterization of miR172/euAP2 genes in Brassica napus L. for likely role in flower organ development

Abstract: Background APETALA2 -like genes encode plant-specific transcription factors, some of which possess one microRNA172 (miR172) binding site. The miR172 and its target euAP2 genes are involved in the process of phase transformation and flower organ development in many plants. However, the roles of miR172 and its target AP2 genes remain largely unknown in Brassica napus ( B. napus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 79 publications
1
12
0
1
Order By: Relevance
“…These vsiRNAs, except “g” may have potential to cleave additional transcript targets (Supplementary Data 6 ). The vsiRNA indexed with “g” (5′-AAGAATCTGATGATGCTGT-3′) shows high sequence similarity to Bna-miR172, which is known to target several AP2-like ethylene response factors (ERFs) 58 , 59 . Consistently, similar to miR172, this vsiRNA had sequence complementarity with transcripts of eight genes encoding ERFs, RAP2–7, TOE2, and APETALA2 (indexed with “g” in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These vsiRNAs, except “g” may have potential to cleave additional transcript targets (Supplementary Data 6 ). The vsiRNA indexed with “g” (5′-AAGAATCTGATGATGCTGT-3′) shows high sequence similarity to Bna-miR172, which is known to target several AP2-like ethylene response factors (ERFs) 58 , 59 . Consistently, similar to miR172, this vsiRNA had sequence complementarity with transcripts of eight genes encoding ERFs, RAP2–7, TOE2, and APETALA2 (indexed with “g” in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another difference is that all the euAP2 proteins contained the unique motif 16, which covered the predicted amino acid sequences of miR172 binding sites ( Figure 2A and Figure S4 ). The miR172 is known to regulate the euAP2 TFs through transcript cleavage in Arabidopsis , rice, and Brassica napus (Chen, 2004; Tang et al, 2007; Wang et al, 2019b), suggesting that miR172 binding sites are conserved in euAP2 genes in plants. Further, we demonstrated that motifs 6, 8, and 9 were exclusively contained in the proteins of the euANT group.…”
Section: Discussionmentioning
confidence: 99%
“…Argonaute ( has expanded, as has the realization that they are highly conserved throughout evolution and that small RNAs can play a direct role in cell-cell signaling (Wang et al, 2019). However, to the best of our knowledge, this is for the first time we report about the involvement of oxidative phosphorylation and spliceosome in the plant resistance against biotic or abiotic stress.…”
Section: Functional Annotation and Kegg Pathway Enrichment Analysis Omentioning
confidence: 88%